Adoption of Social Media for Products Marketing in Algerian Traditional and Handicraft Firms: Evidence from Setif Province - Charchafa, Ilyes; Kimouche, Bilal (Naše gospodarstvo/Our economy, 2025)
Social media provides opportunities for traditional and handicraft industries to promote products and stimulate sales. Therefore, this study investigates the extent of social media adoption for product marketing among a sample of Algerian traditional and handicraft industries. For that, a questionnaire was administered to 123 randomly selected industries in Setif province. The results revealed moderate social media use for product marketing, along with low awareness of its benefits. The level of usage is strongly associated with awareness but was negligibly affected by age. Experience with social media did not predict usage for marketing. The findings suggest that this sector can further capitalise on social media by increasing managers’ awareness of its advantages and developing strategies to enhance its adoption. Further research should identify specific actions that traditional and handicraft firms can take to fully leverage social media for product promotion and sales growth.
Keywords: Social media marketing; Algerian traditional and handicraft; Industry; Products marketing